Evaluation of oral and perioral irritation and sensitization potential of a whitening gel and a whitening toothpaste containing potassium monopersulfate - Li, Yiming; Suprono, Montry S; Cheung, Connie; Ross, Daniella U; Wall, Brian A; Dogo-Isonagie, Cajetan; Arambula, Michele; Xin, Xing (American journal of dentistry, 2023)
Two clinical trials were conducted to investigate the oral and perioral irritation and sensitization potential of a tooth whitening leave-on-gel alone and in combination with a whitening toothpaste, each containing 1.0% of the active ingredient potassium monopersulfate (MPS). Both clinical trials were Institutional Review Board (IRB) approved, double-blind, randomized, and parallel group designed studies. For the MPS leave-on gel study, 200 qualifying and consented subjects were randomly assigned to two groups: (1) 0.1% hydrogen peroxide (H₂O₂) gel pen (34 subjects); and (2) 0.1% H₂O₂ + 1.0% MPS gel pen (166 subjects). Subjects used the assigned products according to instructions provided and returned on Days 22 and 36 for oral and perioral tissue examination (pre-challenge). At the Day 36 visit, the subject applied the assigned gel on site (challenge) and received oral and perioral tissue examinations 1 and 24 hours following the application to detect any post-challenge tissue reactions. For the MPS toothpaste/MPS gel pen study, 200 qualifying and consented subjects were randomly assigned to three groups: (1) Placebo toothpaste + placebo gel pen (66 subjects); (2) 1.0% MPS toothpaste + 1.0% MPS gel pen (67 subjects); and (3) 1.0% MPS toothpaste + placebo gel pen (67 subjects). The study design and procedures were the same as those for the MPS gel pen study described above. For the MPS gel pen study, 192 subjects completed the study. None of the eight dropouts was related to the product use. The demographic data were comparable between the two groups. No evidence of tissue irritation and sensitization was detected in any subjects at any visit, and the findings were comparable between the groups. The detected and self-reported tissue issues were minimal and minor, and they were comparable between the two groups. For the MPS toothpaste/MPS gel pen study, 200 subjects were enrolled with 12 dropped from the study, resulting in an overall dropout rate of 6%. Of the 12 that did not complete the study, none were due to product-related use. The demographic data were comparable among the three groups. The detected and self-reported tissue issues were minimal and minor, and they were comparable among the three groups. Potassium monopersulfate (MPS) at the active concentration of 1.0% in the tooth whitening leave-on-gel and the toothpaste plus the gel did not cause oral/perioral irritation nor sensitization.